Androgen Receptor Imaging in the Management of Hormone-Dependent Cancers with Emphasis on Prostate Cancer - Kairemo, Kalevi; Hodolic, Marina (International journal of molecular sciences, 2023)
Prostate cancer is dependent on the action of steroid hormones on the receptors. Endocrine therapy inhibits hormone production or blocks the receptors, thus providing clinical benefit to many, but not all, oncological patients. It is difficult to predict which patient will benefit from endocrine therapy and which will not. Positron Emission Tomography (PET) imaging of androgen receptors (AR) may provide functional information on the likelihood of endocrine therapy response in individual patients. In this article, we review the utility of [18F]FDHT-PET imaging in prostate, breast, and other hormone-dependent cancers expressing AR. The methodologies, development, and new possibilities are discussed as well.
Keywords: fluorine radioisotopes; Prostatic Neoplasms; glioma; prostata; nádory prostaty; breast cancer; Humans; endocrine therapy; dihydrotestosteron; androgen receptor; Dihydrotestosterone; lidé; therapy response; androgenní receptory; prostate cancer; FDHT; Male; Prostate; Receptors, Androgen; Positron-Emission Tomography; PET; mužské pohlaví; pozitronová emisní tomografie; receptor targeting